Comparing peritoneal dialysis and hemodialysis - patient’s perspective, special consideration of quality of life - Barczuk, Patryk; Bączek, Kacper; Barć, Jan; Bara, Sebastian; Bondos, Borys; Antonik, Jacek; Barczak, Iga; Dzięgielewski, Jędrzej; Gałajda, Elżbieta; Kochan, Robert (Journal of Education, Health and Sport, 2023)
Introduction and purpose: All over the world, patients suffer from chronic kidney disease (CKD) and end-stage kidney disease (ESRD). Patients can choose to undergo hemodialysis in a specialist center or use peritoneal dialysis in their own home. The aim of this study is to answer the question which of the above methods has a better impact on the quality of life of patients. Materials and methods: The literature available on PubMed, Scopus and Google Scholar was reviewed using the words “peritoneal dialysis”; “hemodialysis”; “quality of life”. Description of the state of knowledge: Patients with better physical and emotional functioning have a reduced burden of kidney disease, improved physical ability, pain relief, better overall health, enhanced social function, and more energy. Studies comparing peritoneal dialysis (PD) and hemodialysis (HD) have consistently found that PD is more effective in improving various aspects of quality of life (QOL), such as the physical component score, social component score, cognitive status, emotional function, physical function, body pain, burden of kidney disease, impact of kidney disease on daily life, symptoms/problems, sexual function, finances, and patient satisfaction. Summary: Patients with stage 5 chronic kidney disease who were treated with PD experienced better overall health-related quality of life (HRQoL) compared to patients treated with HD. This result was measured min. using the SF-36 and EQ-5D questionnaires.